What forms of socialization lead women to stop cycling during adolescence? - Sayagh, D.; Dusong, C. (International Review for the Sociology of Sport, 2022)
Cycling in public spaces is both a mobility and a physical activity underpinned by considerable issues, but women practice significantly less, particularly during adolescence. A few studies have sought to study this phenomenon but mainly on the basis of social psychology theories. Based on 84 semi-structured biographical interviews conducted in France, this article aims to discuss their findings using gender, mobility and socialization sociology. We first show how a `feminine` socialization to risk taking, body aesthetics, sport, street and mechanics is an obstacle to cycling during adolescence, especially in the working-class environment and all the more so in spatial contexts with strong norms of male appropriation of public space. We then show how the fact of having cyclists in one's social environment and a sporting inclination plays an important role in limiting the risk of abandonment. By highlighting processes of reinforcement of gendered bodily and spatial inclinations, our results shed light on the links between the socio-construction of inequalities in accessing public space and of inequalities in accessing physical activities. Furthermore, they encourage the study of bicycle socialisation in an intersectional way and suggest the interest of studying the links between urban, ecological, health, sport and mobility socialisations.